2004
DOI: 10.1359/jbmr.040815
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sensitivity of Uterus and Hypothalamus/Pituitary Axis to 17β-Estradiol Is Higher Than That of Bone in Rats

Abstract: We examined the long-term sensitivity of uterus and bone to low-dose 17␤-estradiol in a 4-month experiment in OVX rats and found that a dose of estradiol that fully protected against uterine atrophy did not protect against bone loss. Our results suggest higher estrogen sensitivity of the uterus compared with bone. Introduction: Estrogen is essential for the function of reproductive tissues and for the normal acquisition and maintenance of bone mass in females. This study was designed to examine the long-term s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Furthermore, osteocalcin values were significantly reduced by administration of E 2 in both experimental models. Similar findings have recently been reported that ovx resulted in elevated levels of ALP and osteocalcin, and E 2 supplementation reversed these effects [15,34]. RLX significantly increased osteocalcin levels in the presence of endogenous estrogen, but had decreasing effects in the ovx model.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, osteocalcin values were significantly reduced by administration of E 2 in both experimental models. Similar findings have recently been reported that ovx resulted in elevated levels of ALP and osteocalcin, and E 2 supplementation reversed these effects [15,34]. RLX significantly increased osteocalcin levels in the presence of endogenous estrogen, but had decreasing effects in the ovx model.…”
Section: Discussionsupporting
confidence: 88%
“…# p \ 0.05 for versus SED group, *p \ 0.05 for versus EX group the increase in body weight in the EX-FR group was inhibited, and the uterus weight in the EX-FR group was significantly lower than that in the EX and SED-FR groups. It was reported that low uterus weight can be caused by estradiol deficiency [26]. Thus, in the present study, it may be that rats in the EX-FR group exhibited abnormal estradiol secretion due to low energy availability.…”
Section: Discussionmentioning
confidence: 49%
“…2B). Compared to other tissues, the uterus contains a relatively high number of ERs and, thus, a bioassay of the uterotrophic effects of E2 is considered a highly sensitive test and a positive control for demonstrating E2 action in vivo (Adams et al, 2002; Erben et al, 2004). …”
Section: Resultsmentioning
confidence: 99%